Exploring adaptive capacity to phosphorus challenges through two United Kingdom river catchments. Issue 136 (October 2022) - Lyon, Christopher; Jacobs, Brent; Martin-Ortega, Julia; Rothwell, Shane A.; Davies, Liz; Stoate, Chris; Forber, Kirsty J.; Doody, Donnacha G.; Withers, Paul J.A.
Abstract: Phosphorus (P) is a critical natural resource for food production, but one that is subject to global supply vulnerabilities. P is also responsible for endemic eutrophication in waterbodies due to poor stewardship in the food chain. Catchments are natural social-ecologically bounded systems for P use in agriculture and water management. Stakeholders, such as farmers, water and sewerage service companies, local authorities, and environmental organisations mediate catchment adaptive capacity to P supply risks and P pollution in waterbodies. Adaptive capacity at this level has been insufficiently explored in addressing the P challenge, yet is essential to it. We address this gap by exploring through a qualitative study of stakeholders in two United Kingdom catchments. Our results suggest that the awareness and relevance of P-supply challenges is low in catchments, but the problem of waterbody vulnerability to excess P is of greater concern. Our findings highlight the roles in adaptive capacity of entrenched practices; knowledge and training activities and organisations; stakeholder cooperation and synergy; funding, infrastructure, and technology; the governance environment; and time needed to draw down P. We find that farmers and water companies are especially important to adaptive capacity as they directly interact with P flows. We therefore suggest that catchment adaptive capacity would be significantly improved through a well-supported, and expanded package of existing efforts such as providing scientific evidence of catchment P dynamics; training; payments; more empowered local governance. This effort would support catchment stakeholders to adopt effective P-stewardship practices within a multi-decade integrated catchment management strategy. Highlights: Adaptive capacity of the United Kingdom (UK) study catchments to phosphorus (P) challenges is low but nascent efforts exist Hands-on learning opportunities for farmers show promise for sustainable P management. Strong policy, funding, regulation, training, and stakeholder cooperation are key to building adaptive capacity. Efforts in other jurisdictions, such as New Zealand, may offer insights for the UK.